Pilot study of homologous platelet gel in venous ulcers - de Oliveira, Mariele Gobo [UNESP]; Abbade, Luciana Patricia Fernandes [UNESP]; Miot, Hélio Amante [UNESP]; Ferreira, Rosana Rossi [UNESP]; Deffune, Elenice [UNESP] (FapUNIFESP (SciELO), 2017)
Background: Venous ulcers represent 70% of the lower limb ulcers. They are difficult to heal, requiring a correct diagnostic and therapeutic approach. Many products have been developed to healing, such as homologous platelet gel obtained from the platelet concentrate exceeding from blood transfusion. Objective: To evaluate the safety and efficacy of homologous platelet gel in venous ulcers compared with hydrocolloid dressing. Method: A pilot randomized clinical trial in patients with venous ulcers. Randomized groups (homologous platelet gel and hydrocolloid groups) were followed for 90 days and were assessed through the evolution of ulcerated area, qualitative analysis of vascularization and adverse events. Both groups used elastic compression. Results: We included 16 participants, with a total of 21 venous ulcers. Both treatments promoted a reduction of the areas of the ulcers in 90 days (mean 69%), there was significant difference between the groups concerning the gradual reduction of the ulcers areas, favorably to the hydrocolloid (70% vs 64%; p <0.01). There were some mild adverse events in both groups. Study limitations: Single-center study with a small number of patients, preventing more accurate assessment of the effects of platelet gel. Conclusion: The homologous platelet gel associated with the elastic compression can be an alternative to the venous ulcer treatment and is safe due to the occurrence of a few mild local adverse events and no serious adverse events. Clinical trials with larger numbers of patients must be performed to maintain the indication of this treatment for venous ulcer.
Keywords: Hydrocolloid bandages; Platelet-rich plasma; Varicose ulcer; Wound healing